(untitled) (Anwer Khan Modern Medical College Journal, 2021)
Primary Distal renal tubular acidosis is an infrequent tubular disorder with complex pathophysiology that present with poor growth, skeletal changes and sometimes life-threatening hypokalemia. Here we present two siblings one girl and one boy with a consanguineous parents presented with polyuria, polydipsia, failure to thrive and skeletal deformity. Both cases showed non-anion gap metabolic acidosis with alkaline urine and the younger brother had periodic paralysis due to hypokalemia. After diagnosis and treatment they showed good response with alkali therapy. AKMMC J 2022; 13(1) : 56-59